2022
DOI: 10.1016/j.urology.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Serum PSA Levels in COVID-19 Infected Male Patients with Benign Prostatic Hyperplasia (BPH): A Prospective Cohort Studys

Abstract: Objective To investigate the effect of SARS CoV-2 on serum total PSA levels in men with BPH diagnosed with COVID-19. Methods The PSA (Kit: Immunoassay Program- Cycle 18, Siemens Atellica IM Analyzer) levels in patients who had had a PSA check at least 3 months, but no more than 6 months, prior to diagnosis of acute COVID-19 infection, were examined retrospectively. PSA levels were measured and recorded from these patients on the first day of diagnosis of COVID-19. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The focus of the investigation was the assessment of blood PSA levels in male patients diagnosed with COVID-19, with measurements taken both before the onset of COVID-19 and during the active infection period. Notably, the outcomes demonstrated a concurrence with previous research, revealing similarities across 91 cases in the context of PSA levels [ 25 ]. Overall, it could be observed that the same inflammatory route may contribute to the worsening of BPH-related LUTS and associated consequences both during and after infection with SARS-CoV-2 [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…The focus of the investigation was the assessment of blood PSA levels in male patients diagnosed with COVID-19, with measurements taken both before the onset of COVID-19 and during the active infection period. Notably, the outcomes demonstrated a concurrence with previous research, revealing similarities across 91 cases in the context of PSA levels [ 25 ]. Overall, it could be observed that the same inflammatory route may contribute to the worsening of BPH-related LUTS and associated consequences both during and after infection with SARS-CoV-2 [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…Multiple studies have explored this space and it does not appear that SARS-CoV-2 infection is associated with an increase in prostate cancer 54 . In contrast, another study suggests that infection with SARS-CoV-2 may be associated with an increase in prostate specific antigen (PSA) detection in plasma 55 .…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have explored this space and it does not appear that SARS-CoV-2 infection is associated with an increase in prostate cancer 54 . In contrast, another study suggests that infection with SARS-CoV-2 may be associated with an increase in prostate specific antigen (PSA) detection in plasma 55 . Future studies are needed to confirm whether the robust signal of the SARS-CoV-2 PET/CT probe reflects a high-level infection of the human prostate and its subsequent impact on male sexual health and fertility 56, 57 .…”
Section: Discussionmentioning
confidence: 97%
“…Another topic still being debated is PSA in COVID-19 patients. Cinislioglu et al [ 8 ] found that SARS-CoV-2 infection in men diagnosed with BPH caused significant increases in PSA levels during the active period of the disease. The authors provided as an explanation that SARS-COV-2 induces tissue damage in the prostate and down-regulation of ACE2.…”
Section: Discussionmentioning
confidence: 99%